2018
DOI: 10.4314/gmj.v52i1.4
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of spacer device, peak flow meter and inhaler technique (MDIs) among health care providers: an evaluation of doctors and nurses.

Abstract: self-funded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…16 17 A recent study found only 12% of healthcare workers knew at least three essential steps of the correct metered-dose inhaler technique, and none of the participants performed all the steps correctly. 18 For the checklist, we used a standardised protocol recently published in Dutch healthcare. Although this protocol is based on the existing literature, a few instruction steps are only marginally substantiated by research data, and we needed to make a few assumptions about the best spray technique (table 4).…”
Section: Discussionmentioning
confidence: 99%
“…16 17 A recent study found only 12% of healthcare workers knew at least three essential steps of the correct metered-dose inhaler technique, and none of the participants performed all the steps correctly. 18 For the checklist, we used a standardised protocol recently published in Dutch healthcare. Although this protocol is based on the existing literature, a few instruction steps are only marginally substantiated by research data, and we needed to make a few assumptions about the best spray technique (table 4).…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to findings in studies on paediatric residents in other countries and amongst other specialties and health workers, in various countries including Nigeria. [13][14][15][16] About 84% of Nigerian doctors in Owo, Ondo state Nigeria and 85.8% of Spanish physicians had poor knowledge of inhaler technique. [10,16] The Nigerian study however, required practical demonstration of the basic steps in MDI technique while the Spanish study was a similar questionnaire based study where the knowledge score Despite this, the study done recently to assess their knowledge still revealed a paucity of knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16] About 84% of Nigerian doctors in Owo, Ondo state Nigeria and 85.8% of Spanish physicians had poor knowledge of inhaler technique. [10,16] The Nigerian study however, required practical demonstration of the basic steps in MDI technique while the Spanish study was a similar questionnaire based study where the knowledge score Despite this, the study done recently to assess their knowledge still revealed a paucity of knowledge. 10 With the efficacy of inhaled medication being largely dependent on the right technique of use by patients for deposition of the appropriate drug dose at the target site, this paucity of knowledge of physicians is inimical to the achievement of optimal asthma control.…”
Section: Discussionmentioning
confidence: 99%
“…Banzene, Naphta, Ammonia and chlorine gas, acetic acid, Methanol, Epichlorohydrin and Methyl ethyl ketone have highest risk based on several studies which were conducted on the health risk of occupational exposure of chemicals in Iran petrochemical industry. Based on studies carried out in Saudi Arabia and Nigeria, the prevalence of respiratory symptoms in workers engaged in petrochemicals is more than the control group; also, the pulmonary function indices in exposed workers are lower than the control group (6,7). Investigating the prevalence of respiratory symptoms and airflow obstruction diseases in petrochemical workers is done by spirometry through a series of experiments on pulmonary function tests (PFTS).Spirometry has a significant role in the diagnosis and prognosis of pulmonary diseases (obstruction or restriction).…”
mentioning
confidence: 99%
“…Even, if workers appear normal clinically (8). Studies conducted on pulmonary function indices in exposed subjects have shown a significant reduction in some pulmonary function parameters (of forced vital capacity (FVC), forced expiratory volume in the first second (FEV1), peak expiratory flow (PEF), forced expiratory flow (FEF) 25%, and forced expiratory flow (FEF) 50%) (6,7). In order to achieve health goals for protection of labor, preventing, deciding on control measures and reducing the risk of exposure to chemicals in the workplace, it is necessary that exposure of people to chemicals and the risks which were caused by these substances to be examined.…”
mentioning
confidence: 99%